2013
DOI: 10.1002/jmr.2257
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of specific and nonspecific DNA by human lactoferrin

Abstract: The general principles of recognition of nucleic acids by proteins are among the most exciting problems of molecular biology. Human lactoferrin (LF) is a remarkable protein possessing many independent biological functions, including interaction with DNA. In human milk, LF is a major DNase featuring two DNA-binding sites with different affinities for DNA. The mechanism of DNA recognition by LF was studied here for the first time. Electrophoretic mobility shift assay and fluorescence measurements were used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In contrast to DNA polymerases, uracil‐DNA glycosylase (Vinogradova et al, ) AP endonuclease, and topoisomerase I (Topo I), but similarly to Escherichia coli 8‐oxoguanine DNA glycosylase (Fpg), human 8‐oxoguanine DNA glycosylase (OGG1), and Eco RI endonuclease, the affinity of human lactoferrin for d(pC) n , d(pT) n , and d(pA) n homo‐ODNs did not depend on the bases and their relative hydrophobicity; it depended only on the number of internucleoside phosphate groups . HIV‐1 integrase was the first enzyme, in which the affinity for nonspecific d(pC) n , d(pT) n , and d(pA) n was dependent on the bases but did not follow their relative hydrophobicity .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to DNA polymerases, uracil‐DNA glycosylase (Vinogradova et al, ) AP endonuclease, and topoisomerase I (Topo I), but similarly to Escherichia coli 8‐oxoguanine DNA glycosylase (Fpg), human 8‐oxoguanine DNA glycosylase (OGG1), and Eco RI endonuclease, the affinity of human lactoferrin for d(pC) n , d(pT) n , and d(pA) n homo‐ODNs did not depend on the bases and their relative hydrophobicity; it depended only on the number of internucleoside phosphate groups . HIV‐1 integrase was the first enzyme, in which the affinity for nonspecific d(pC) n , d(pT) n , and d(pA) n was dependent on the bases but did not follow their relative hydrophobicity .…”
Section: Resultsmentioning
confidence: 98%
“…d(pA) 8 2.2 × 10 −8 6.7 × 10 −7 d(pC) 6 1.0 × 10 −8 7.9 × 10 −7 d(pT) 6 1.0 × 10 −9 2.7 × 10 −7 d(pA) 9 2.2 × 10 −8 4.5 × 10 −7 d(pC) 8 3.7 × 10 −9 6.6 × 10 −7 d(pT) 8 1.1 × 10 −8 2.3 × 10 −7 d(pA) 10 2.1 × 10 −8 3.5 × 10 −7 d(pC) 9 3.5 × 10 −9 4.6 × 10 −7 d(pT) 10 1.4 × 10 −8 2.4 × 10 −7 d(pA) 12 1.9 × 10 −8 3.4 × 10 −7 d(pC) 10 3.2 × 10 −9 3.9 × 10 −7 d(pT) 11 1.4 × 10 −8 2.9 × 10 −7 d(pA) 13 1.9 × 10 −8 3.1 × 10 −7 d(pC) 12 3.1 × 10 −9 3.8 × 10 −7 d(pT) 16 1.3 × 10 −8 2.0 × 10 −7 d(pA) 15 1.9 × 10 −8 2.9 × 10 −7 d(pC) 14 2.9 × 10 −9 3.6 × 10 −7 d(pT) 24 1.3 × 10 −8 1.6 × 10 −7 d(pA) 16 1.9 × 10 −8 2.3 × 10 −7 d(pC) 16 3.0 × 10 In contrast to DNA polymerases, [10][11][12][13] uracil-DNA glycosylase (Vinogradova et al, 25 ) AP endonuclease, 16 and topoisomerase I (Topo I), 19,20 but similarly to Escherichia coli 8-oxoguanine DNA glycosylase (Fpg), 23,27 human 8-oxoguanine DNA glycosylase (OGG1), 24 and EcoRI endonuclease, 15 the affinity of human lactoferrin for d(pC) n , d(pT) n , and d(pA) n homo-ODNs did not depend on the bases and their relative hydrophobicity; it depended only on the number of internucleoside phosphate groups. 22 HIV-1 integrase was the first enzyme, in which the affinity for nonspecific d(pC) n , d(pT) n , and d(pA) n was dependent on the bases but did not follow their relative hydrophobicity. 21 The affinity of d(A) n and d(C) n (having minimal and maximal relative hydrophobicity) was similar, while the affinity of d(T) n was significantly lower.…”
Section: Interaction Of Iggs With Nucleotide Units Of Single-strandmentioning
confidence: 99%
See 1 more Smart Citation
“… To evaluate the relative contributions of individual DNA elements to the enzyme affinity for long polymeric and oligomeric ligands, a new approach, stepwise increase in ligand complexity (SILC), was developed . Using the SILC, we have analyzed the mechanisms of recognition of DNA by number of DNA‐dependent enzymes: not specific for DNA sequence and structure such as Escherichia coli RecA, specific for DNA structure but not sequence‐dependent such as DNA polymerases of eukaryotes, prokaryotes, viruses, and archaea and human DNA ligase I; specific for DNA containing damages such as human uracil DNA glycosylase, E. coli Fpg and human 8‐oxoguanine DNA glycosylases (OGG1), human apurinic/apyrimidinic endonuclease (AP endonuclease), as well as specific for DNA sequence such as human HIV integrase, topoisomerase I (Topo I), Eco RI restriction endonuclease, and human lactoferrin (LF) . It was shown that complex formation including formation of contacts between specific sequences in all these enzymes cannot provide for either substrate specificity or high enzyme affinity for DNA.…”
Section: Introductionmentioning
confidence: 99%
“…human lactoferrin (LF). 20 It was shown that complex formation including formation of contacts between specific sequences in all these enzymes cannot provide for either substrate specificity or high enzyme affinity for DNA. All these enzymes recognize DNA by the formation of multiple additive contacts with all DNA nucleotide units covered by the protein globule (7-20 units depending on the enzyme).…”
mentioning
confidence: 99%